2000
DOI: 10.1056/nejm200009143431104
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Factor VII Gene and the Risk of Myocardial Infarction in Patients with Coronary Artery Disease

Abstract: Our findings suggest that certain factor VII genotypes have a role in protection against myocardial infarction. This may explain why some patients do not have myocardial infarction despite the presence of severe coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
140
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 31 publications
(28 reference statements)
16
140
2
3
Order By: Relevance
“…24 On the other hand, certain factor VII genotypes associated with lower plasma factor VII levels (and thus lower prothrombinase activity) are thought to protect against myocardial infarction. 25 Platelets express this procoagulant activity in response to collagens or CVX in a dose-dependent manner, as reported by Alberio et al 11 and confirmed by our results in the present study. At 2 different concentrations (14.7 and 22 ng/mL), CVX induced prothrombinase activity in a dose-dependent manner.…”
Section: Furihata Et Alsupporting
confidence: 93%
“…24 On the other hand, certain factor VII genotypes associated with lower plasma factor VII levels (and thus lower prothrombinase activity) are thought to protect against myocardial infarction. 25 Platelets express this procoagulant activity in response to collagens or CVX in a dose-dependent manner, as reported by Alberio et al 11 and confirmed by our results in the present study. At 2 different concentrations (14.7 and 22 ng/mL), CVX induced prothrombinase activity in a dose-dependent manner.…”
Section: Furihata Et Alsupporting
confidence: 93%
“…Details about the enrolment criteria have been described elsewhere. 14 In the present study, we examined data from a total of 1431 subjects, for whom complete analyses of seven ALOX5AP SNPs (see below) were available. Of these subjects, 1047 had angiographically documented severe coronary atherosclerosis (CAD group), the majority of them being candidates for coronary artery bypass grafting or percutaneous coronary intervention.…”
Section: Study Populationmentioning
confidence: 99%
“…It is shown the clinical value of two polymorphisms of the gene: R353Q 10976 G4A and À323 ins 10 bp (insertion of 10 nucleotides in promoter region). The presence of the minor allele of the gene has a proven protective effect against the development of thrombosis and cardiovascular diseases [68]. In case of SNP 10976 G4A allele A presence enzyme activity is reduced and in case of insertions in the promoter of the gene expression level decreases.…”
Section: Snps In the Renin-angiotensin Systemmentioning
confidence: 99%